EVALUASI KEBIJAKAN RETRIBUSI IZIN MENDIRIKAN BANGUNAN (IMB) DI KABUPATEN MAMUJU UTARA - Mansur, Mansur (Katalogis, 2016)
The objective of this study is to evalute the extent of policy effectiveness retribution building permits (IMB) in Mamuju utara regency. Data Collection was done by using observation and in-depth interviews, while the technique of data analysis include data reduction, display the data and draw conclusions and verification using qualitative descriptive analysis. The results showed the retribution policy performance of building permits (IMB) in Mamuju utara regency has not two aspects of evaluation criteria is performing well or which, in common criteria and the criteria accuary. While the four aspects of evaluation criteria is not maximized performance criteria of effectiveness, efficiency,Â Adequacy, and responsiveness. From local regulation number 27 ofÂ 2011 concering the retribution of building permits due to lack of. Socialization to the people who made the implementor. lack of supervision and weak enforecement of sanctions for people who violate the provisions of the policy of building permit retribution.